Implementasi Standar Pengelolaan Pendidikan Sekolah Dasar Negeri 1 Jembe Kecamatan Janapria Tahun Ajaran 2019/2020 - Samsul Rizal; Taufiqurrahman Usman; Azhar Azhar; Yenda Puspita (South Sulawesi Education Develoment (SSED), 2019)
This study describes the implementation of management standards of education in SDN 1 Jembe. Concerning about the school program planning, implementation plan of school programs, monitoring and evaluation, the leadership of headmaster. This study used a qualitative approach. Data were obtained from principals, vice-principals, heads of administration, teachers, and students. The research data obtained by triangulation techniques through observation, interviews, and document research. The results of this study revealed five findings are: 1) Planning program at SDN 1 Jembe are in accordance with the Education Management Standards but based on the research, SDN 1 Jembe not done a SWOT analysis. While the school has a strategic plan for the school, but the school strategic plan is not based on in-depth analysis in advance. 2) Implementation of the program at SDN 1 Jembe an aspect which is more dominant than the other standard component of education management. 3) Monitoring and evaluation at SDN 1 Jembe carried out in accordance with the rules on the implementation of management standards. forms of monitoring and evaluation at SDN 1 Jembe implemented through the preparation of a monitoring program on the aspects of the implementation of the SBC and the performance of educators by the school principal, 4) Leadership in SDN 1 Jembe is in conformity with the standards management of education because it consists of the principals assisted by four deputies, although supposed to be composed of five vice-principals.